International Journal of Disaster Risk Science - Shi, Pei Jun; Jaeger, Carlo; Li, Ying
The International Journal of Disaster Risk Science (IJDRS) provides a pioneering platform for researchers and practitioners aiming at greater resilience and integrated risk governance in view of local, regional, and global disasters. IJDRS breaks new ground in research about disaster risks by connecting in-depth studies of actual disasters and of specific practices of disaster risk management with investigations of the global dynamics of disaster risks and theories and models relevant for advanced integrated risk governance. The journal’s primary aim is to enable the disaster risk community to communicate, learn, and progress in order to improve the capacities for integrated disaster risk and resilience identification, measurement, and governance at all scales. IJDRS is an interdisciplinary English language journal that publishes research articles that are problem-driven and solution-oriented, providing insights on major disasters in a timely fashion and addressing theoretical and methodological issues in disaster risk science. Topics ·         Human dimensions of disaster risk ·         Disaster risk governance and resilience ·         Disaster risk and resilience indicators and measurement ·         Global change and disaster risks ·         Development and risk transition ·         Empirical studies and perspectives on major disaster events.